Servants of the kingdom : professionalization among ministers of the nineteenth-century Netherlands Reformed Church - Bos, David (Brill's series in church history, 2010)
Minister of the Word, shepherd and teacher--the titles of Dutch pastors exude authority and prestige. In the course of the nineteenth century, however, their social position was slowly undermined by the separation of church and state, the emancipation of Catholics and dissenters, and the rise of all sorts of secular ""shepherds"" and ""teachers."" This work of historical sociology analyzes the development of the profession of pastor in the Netherlands Reformed Church, focusing on pastors' changing relationships with the state, the universities, other professions, and their own congregants. It